Conflict of Eastern and western civilization in Pakistani stage (published ) dramas - Shagufta Khurshid (بازیافت)
The article deals with the elements of the conflicts between the eastern and the western civilizations in stage plays of Urdu language. After the coming into being of Pakistan, it had its own civilization which was mostly based on the golden principles of Islam including positive aspects of eastern civilization.The western civilization brought by the British had a profound effect on the eastern civilization Pakistan as well as of subcontinent. Its effected or influenced the Pakistani people as well. Even at present time, our society is under its spell.  Some people show love for eastern civilization.The utilitarian aspects of western civilization can be adopted, but there is a fear of damaging the foundations of eastern civilization, because there is a clash between these two civilizations. Our Pakistani stage playwrights have pointed out such social and cultural issues in their plays as well as the display of eastern and western civilizations. It can be seen conflicts of religious elements, co-education, dress, unparalleled freedom of women in their plays.  Among the stage playwrights, Khwaja Moinuddin, Mirza Adib, Kamal Ahmad Rizvi, Agha Nasir, Javed Iqbal, Hijab Imtiaz Ali, have portrayed the clash of these two civilizations in their plays. Showing conflicts they have indirectly suggested to follow the eastern civilization instead of western civilization.